Transcriptomic analysis identified up-regulation of a solute carrier transporter and UDP glucuronosyltransferases in dogs with aggressive cutaneous mast cell tumours. (June 2016) - Giantin, Mery; Baratto, Chiara; Marconato, Laura; Vascellari, Marta; Mutinelli, Franco; Dacasto, Mauro; Granato, Anna
Highlights: Aggressive mast cell tumour transcriptome has been characterised by DNA microarray. Eight target genes differentiate aggressive from not aggressive mast cell tumours. Drug metabolism and cell cycle pathways characterise aggressive mast cell tumours. We propose SLCs and UGTs as potential targets for the biological behaviour prediction of canine cutaneous mast cell tumour. Abstract: Gene expression analyses have been recently used in cancer research to identify genes associated with tumorigenesis and potential prognostic markers or therapeutic targets. In the present study, the transcriptome of dogs that had died because of mast cell tumours (MCTs) was characterised to identify a fingerprint having significant influence on prognosis determination and treatment selection. A dataset (GSE50433) obtained using a commercial canine DNA microarray platform was used. The transcriptome of seven biopsies obtained from dogs with histologically confirmed, surgically removed MCTs, treated with chemotherapy, and dead for MCT-related causes, was compared with the transcriptional portrait of 40 samples obtained from dogs with histologically confirmed, surgically removed MCTs and that were still alive at the end of the follow-up period. Among the differentially expressed genes (DEGs), eight transcripts were validated by quantitative real time PCR and their mRNA levels were measured in a cohort of 22 additional MCTs. Statistical analysis identified 375 DEGs (fold change 2, false discovery rate 5%). The functional annotation analysis indicated that the DEGs were associated with drug metabolism and cell cycle pathways. Particularly, members of solute carrier transporter (SLC) and UDP glucuronosyltransferase (UGT) gene families were identified as dysregulated. Principal component analysis (PCA) of the 22 additional MCTs identified the separate cluster dogs dead for MCT-related causes. SLCs and UGTs have been recently recognised in human cancer as important key factors in tumour progression and chemo-resistance. An in-depth analysis of their roles in aggressive canine MCT is warranted in future studies.